2021
DOI: 10.3389/fimmu.2021.645446
|View full text |Cite
|
Sign up to set email alerts
|

Antiretroviral Treatment-Induced Decrease in Immune Activation Contributes to Reduced Susceptibility to Tuberculosis in HIV-1/Mtb Co-infected Persons

Abstract: Antiretroviral treatment (ART) reduces the risk of developing active tuberculosis (TB) in HIV-1 co-infected persons. In order to understand host immune responses during ART in the context of Mycobacterium tuberculosis (Mtb) sensitization, we performed RNAseq analysis of whole blood-derived RNA from individuals with latent TB infection coinfected with HIV-1, during the first 6 months of ART. A significant fall in RNA sequence abundance of the Hallmark IFN-alpha, IFN-gamma, IL-6/JAK/STAT3 signaling, and inflamma… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 41 publications
3
7
0
Order By: Relevance
“…One limitation of our study was that we did not have an ART-naïve group of SIV-infected juveniles with which to directly compare the effect of ART on TB pathogenesis in SIV-infected juvenile macaques. There is ample evidence in humans (69, 70, 78) that supports our hypothesis that ART may have restored anti-Mtb immunity and control of TB in SIV-infected juvenile macaques. ART previously was shown to reduce the risk of SIV-induced reactivation of latent TB infection (LTBI) in adult macaques (71), and ART may be an important tool to reduce TB reactivation in HIV+ people with LTBI (84).…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…One limitation of our study was that we did not have an ART-naïve group of SIV-infected juveniles with which to directly compare the effect of ART on TB pathogenesis in SIV-infected juvenile macaques. There is ample evidence in humans (69, 70, 78) that supports our hypothesis that ART may have restored anti-Mtb immunity and control of TB in SIV-infected juvenile macaques. ART previously was shown to reduce the risk of SIV-induced reactivation of latent TB infection (LTBI) in adult macaques (71), and ART may be an important tool to reduce TB reactivation in HIV+ people with LTBI (84).…”
Section: Discussionsupporting
confidence: 77%
“…One limitation of our study was that we did not have an ART-naïve group of SIV-infected juveniles with which to directly compare the effect of ART on TB pathogenesis in SIV-infected juvenile macaques. There is ample evidence in humans (69,70,78) that supports our hypothesis that ART may have restored anti-Mtb immunity and control of TB in SIV-infected juvenile macaques.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…reported that the inflammatory cytokines IL‐1β, IL‐6, TNF‐α were elevated in the serum of HIV‐1 patients and there was a positive correlation between the level of these cytokines and the levels of viral RNA 186 . Although ART seems to be able to significantly decrease the serum levels of such cytokines in HIV‐1 patients, their levels are still significantly higher than the normal uninfected controls 186,187 . In line with these results, a recent study conducted by Masyuko et al., who enroled 286 HIV‐1 positive Kenyan adults with suppressive ART for several years, reported that HIV‐1 patients express higher serum levels of the inflammatory cytokines IL‐1β, IL‐6, TNF‐α than the uninfected controls, even when the virus is fully suppressed 188 .…”
Section: The Impact Of Antiretroviral Therapy On Il‐1β In Human Immun...mentioning
confidence: 72%
“…186 Although ART seems to be able to significantly decrease the serum levels of such cytokines in HIV-1 patients, their levels are still significantly higher than the normal uninfected controls. 186,187 In line with these results, a recent study conducted by Masyuko et al, who enroled 286 HIV-1 positive Kenyan adults with suppressive ART for several years, reported that HIV-1 patients express higher serum levels of the inflammatory cytokines IL-1β, IL-6, TNF-α than the uninfected controls, even when the virus is fully suppressed. 188 On the contrary, other studies showed that treatment with ART has no effect on decreasing the expression of several proinflammatory cytokines including IL-1β.…”
Section: The Impact Of Antiretroviral Therapy On Il-1β In Human Immun...mentioning
confidence: 72%